Diffusion Disk Susceptibility Testing with Cefotaxime - Aswapokee, Nalinee (1979)
The diffusion disk susceptibility of Staphylococcus aureus, Enterobacteriaceae, and Pseudomonas aeruginosa to cefotaxime was determined. A 30-μg disk provided data for the susceptibility of P. aeruginosa, but yielded extremely large zones of inhibition against Enterobacteriaceae. A 5-μg disk seemed to provide the most useful susceptibility data for S. aureus and Enterobacteriaceae.